Application of error correction models for Lithuanian inflation - Čuvak, Ana; Kalinauskas , Žilvinas (Lietuvos matematikos rinkinys, 2008)
This paper is devoted to the Lithuanian inflation modelling. The main goal of this work is to apply Vector Error Correction Model for Lithaunian inflation. All inflation indicators are integrated of order one, consequently VECM model of Lithuanian inflation processes is investigated and proposed for modelling.